UPAYA MENINGKATKAN KETERAMPILAN MENULIS HURUF JAWA MELALUI DISKUSI KELOMPOK BERBANTU KARTU HURUF PADA PESERTA DIDIK KELAS VI SD 1 PRAMBATAN KIDUL KUDUS - S. Sulistyani (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2020)
The study aims to improve the student skills in writing The Javanese Script and learning activities through group discussion assisted by letter cards in the 6th-grade students of SD 1 Prambatan Kidul Kudus Even Semester Academic Year 2018/2019. This study is a Classroom Action Research (CAR) conducted in two cycles using The Javanese Script cards as the learning media and group discussion as the learning method. Research data were collected using nontest techniques (classroom observation, unstructured interviews, and documentation collection) and test techniques (individual written tests). Quantitative data were the scores of The Javanese Script writing skill were analyzed descriptively and qualitative data were the result of learning activities observations that converted into scores and categorized classically. The Pre-cycle stage test score category consisted of poor (62.16%) and fair scores (37.84%), with students had reached learning mastery standard by 37.84%. The Cycle I stage test score category consisted of poor (27.03%), fair (56.76%), and good scores (16.22%), with students had reached learning mastery standard by 72.97%. The Cycle II stage test score category consisted of fair (48.65%), good (40.54%), and very good scores (10.81%), with students had reached learning mastery standard by 100%. The classical learning activities observations are classified as good, both in Cycle I and Cycle II were 70.27% and 71.89%, respectively. Thus, the method of group discussion assisted by letter cards is proven to improve the student skills in writing The Javanese Script and learning activities.